Educational achievements: Does the gender of students matter? - María María Ibañez Martín; María Marta Formichella (Arizona State University, 2017)
There are different factors that influence educational outcomes of students and these factors can help in decision-making and policy development. In this context, this paper analyzes whether differences in school achievement are able to be explained by considering the gender of the students. For this purpose, PISA data bases corresponding to all waves in which Argentina has participated and a multilevel trivariate econometric methodology were used, suggesting evidence for the existence of differences in educational attainment between men and women.